Development of Test Instruments Based on Critical Thinking Skills for Measuring Students' Minimum Competency in Thermochemical Materia - Achdah Rachmatul Bariyah (Chemistry in Education, 2024)
The changes in 21st century life force students to quickly adapt in the field of education, especially in critical thinking skills and minimum competencies. This study aims to develop a test instrument based on critical thinking skills to analyze the minimum competency level of students. The research method is Research and Development with a 4D development design (Define, Design, Develop, and Disseminate). The subjects of the study were students of class XI MIPA SMA Muhammadiyah 1 Temanggung. Data collection methods consist of observation and testing of test instrument designs. Data collection instruments use interview sheets, documentation, test instruments, expert validation sheets, and questionnaire response sheets. Test and non-test data analysis techniques are analysis of the feasibility of test instruments, validity and reliability estimation, measurement of minimum competency levels, and analysis of student questionnaire responses. The results of the observation stated that teachers had implemented the Minimum Competency Assessment test but it was not optimal. The results of the instrument feasibility study were valid based on expert validation. The validity of the questions contained one misfit question. The reliability of the questions tended to be good. The results of the competency level analysis obtained 22% proficient, 26% capable, 28% basic, and 24% need special intervention. The results of the student questionnaire responses stated that they agreed that the instrument was feasible and successful to use. The conclusion of the instrument from the development was tested for feasibility, content validity, and a positive response was obtained.